2017
DOI: 10.1080/10376178.2017.1338525
|View full text |Cite
|
Sign up to set email alerts
|

Determining the key drivers and mitigating factors that influence the role of the Nurse and/or Midwife Consultant: a cross-sectional survey

Abstract: Understanding the key drivers and mitigating factors that influence the role of the Nurse and/or Midwife Consultant is important for healthcare managers. Given the changing landscape of nursing and midwifery practice, organisational strategies to provide ongoing support to address the mitigating factors are urgently needed. It is pivotal that nursing management implement strategies to empower Nurse and/or Midwife Consultants to perform and reach their potential to deliver advanced nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Where most specialist nurse participants in this study believed that they had the support of their medical colleagues, they speculated that their nursing colleagues either did not understand their role or did not support their advanced level of practice. A survey by Fernandez et al (2017) of 122 nurse or midwife consultants in New South Wales, Australia also found that while nurse and midwife consultants believed that their medical colleagues and other multidisciplinary team members accepted and understood their role, they saw a lack of understanding from their nursing colleagues as a limiting factor to their effective performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where most specialist nurse participants in this study believed that they had the support of their medical colleagues, they speculated that their nursing colleagues either did not understand their role or did not support their advanced level of practice. A survey by Fernandez et al (2017) of 122 nurse or midwife consultants in New South Wales, Australia also found that while nurse and midwife consultants believed that their medical colleagues and other multidisciplinary team members accepted and understood their role, they saw a lack of understanding from their nursing colleagues as a limiting factor to their effective performance.…”
Section: Discussionmentioning
confidence: 99%
“…A survey by Fernandez et al. (2017) of 122 nurse or midwife consultants in New South Wales, Australia also found that while nurse and midwife consultants believed that their medical colleagues and other multidisciplinary team members accepted and understood their role, they saw a lack of understanding from their nursing colleagues as a limiting factor to their effective performance. Previous studies have identified that management support was a major facilitator and indicator of the success of clinical nurse specialist roles (Black & Farmer, 2013; Bousfield, 1997; Kilpatrick et al., 2016; Leary et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given the origins and strong person-centered focus of the profession, this is not surprising. This finding is echoed in a number of Australian and international publications where researchers identified the main motivations for the profession's drive toward expansion of scope were improved professional satisfaction, patient need (Fernandez, Sheppard-Law, & Manning, 2017), geographical limitations to patient access to medical, pharmacy, and allied health practitioners (Hegney, 1997), and management of increasing public health expenditure (Tsiachristas et al., 2015). A continued emphasis on person-centered approaches embedded in nursing practice, particularly as part of preparatory and continuing educational programs, would ensure that the power of this phenomenon is harnessed.…”
Section: Discussionmentioning
confidence: 99%
“…DoNs highlighted that, in newly introduced roles and without evidence to support their impact, the individual characteristics of NCs are likely to be particularly important, as reported in other studies. McIntosh and Tolson () cited the need for NCs to have strong interpersonal skills and capacity for intellectual effort in order to meet the demands of the role, whilst (Fernandez, Sheppard‐Law, & Manning, ) reported Australian nurse consultants' views that that personal attributes, including motivation and communication skills, were key drivers to role performance.…”
Section: Discussionmentioning
confidence: 99%